Mechanical Properties Measurement of Polymer Films by Bulge Test and Fringe Projection - C. S. Lin; T. L. Horng; J. H. Chen; K. H. Chen; J. J. Wu; C. Y. Chen; S. H. Ma (Advances in Materials Science and Engineering)
This paper aims at determining the mechanical properties such as Poisson ratio, biaxial modulus, and residual stress of polymer membranes using the bulge test and fringe projection. Under this idea, a bulge test apparatus has been developed for robust usage, under the room temperature, in industrial environments that are usually noisy and full of all kinds of vibrations. A setup of the bulge test, consisting of single chips and digital on-off valves, was used to achieve automatic precision control of pressure application to gas chamber with a circular polyimide (PI) test film fixed on the opening of it. A deformed image was then obtained via fringe projections with a series of optical apparatuses, and a 3D membrane deformation distribution was further achieved from this deformed image by some image processes that are chiefly through wavelet transformation and phase expansion. With the measurements of maximum membrane deformation versus applied pressure and given the Young’s modulus of test membrane, we could further calculate the Poisson ration (and then biaxial modulus) and residual stress of the film. Also, the measurements were validated to be highly accurate by comparison with a finite element analysis.